METHODOLOGICAL APPROACHES AIMED AT MEETING THE PERSONAL NEEDS OF CHILDREN IN THE PROCESS OF INCLUSIVE EDUCATION - Abdullaeva Lola Tohirovna; Eny Syatriana (Universitas Muhammadiyah Makassar, 2025)
The article explores the history, meaning, and importance of inclusive education; outlines its methodological underpinnings, aims, and objectives; and supports the humanistic nature of the pedagogical principles and conceptual ideas of inclusive education as well as their potential for application.